Оптимизация расположения межслойных переходов на группе проводников - Sadchenko , A. V.; Kushnirenko, O. A.; Troyansky, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2015)
The problem of technical implementation of phased array antennas (PAR) with the required radiation pattern (RP) is the complexity of the construction of the beam forming device that consists of a set of controlled attenuators and phase shifters. It is possible to simplify the technical implementation of PAR, if complex representation of coefficients of amplitude-phase distribution of the field along the lattice is approximated by real values in the synthesis stage. It is known that the amplitude distribution of the field in the aperture of the antenna array and the radiation pattern are associated with Fourier transform. Thus, the amplitude and phase coefficients are first calculated using the Fourier transform, and then processed according to the selected type of circuit realization of attenuators and phase shifters. The calculation of the inverse Fourier transform of the modified coefficients allows calculating the synthesized orientation function. This study aims to develop a search algorithm for amplitude and phase coefficients, taking into account the fact that integer-valued amplitudes and phases are technically easier to implement than real ones. Synthesis algorithm for equidistant linear array with a half-wavelength irradiators pitch (λ/2) is as follows. From a given directivity function the discrete Fourier transform (DFT) in the form of an array of complex numbers is found, the resulting array is then transformed into a set of attenuations for attenuators and phase shifts for phase shifters, while the amplitude coefficients are rounded off to integers, and phases are binarizated (0, π). The practical value of this algorithm is particularly high when using controlled phase shifters and attenuators integrally. The work confirms the possibility of a thermoelectric converter of human body application for an electronic medical thermometer power supply.